Urbanization And Sustainability: Designing For The Future – A Case Of Guwahati - Pathak, Jagriti; Buragohain, Jayantajit (MAJ - Malaysia Architectural Journal, 2025)
This research paper aims to provide insights into encountering the rapidly increasing density with sustainable development and how by maintaining a correlation between the same one can address the welfare, well beings of all living beings inhabiting that place. The linking of demographic factors with sustainability helps us to address the various ignored and excluded factors that in the long term hampers the livelihood of people of all age groups. It also helps in planning development considering the ecological limits of the earth. The paper also emphasizes the crucial role of architects as they help in shaping the built environment which is the fundamental component of every community. Architects and Urban Planners through their design can inculcate the concept of sustainability in the community and fulfill both the roles as responsible citizens and professionals thereby becoming sustainable members of their community. The paper aims to identify the various needs and requirements of people belonging to all age groups by conducting an online survey tool like Google Form that will be circulated among 96 people randomly chosen between the age group of 18 -70 years residing in the various parts of Guwahati City ( Municipal Boundary). This study will help identify the loopholes in the system thus helping the designers and planners to create a sustainable environment. Therefore, this study's conclusion emphasizes designing spaces that promote inculcating environmentally conscious behavior among people and also creating opportunities for interactions between humans and nature. It also focuses on generating awareness among people of age groups both at the micro and macro level in discouraging any development that hampers the immediate and more distant environments.